Relationship of Body Mass Index (BMI) with the Incidence of Inguinal Hernia: Relationship of Body Mass Index (BMI) with the Incidence of Inguinal Hernia - Hussain, Zahoor; Ali Lashari, Azad; uddin, Siraj; Ali Bijarani, Farman; Hussain Memon, Aijaz; Chandio, Sadaf (Pakistan Journal of Health Sciences, 2022)
The inguinal wall hernia is the communal hernia of the abdominal wall. It is a communal disorder that affects both males and females from the past long duration. Objective: To assess the incidence of unilateral or bilateral inguinal hernia with low body mass index (BMI) and normal BMI subjects. Methods: This study was performed in the Surgical unit 1 of Khairpur Medical College and civil Hospital Khairpur Mirs for one-year duration from July 2021 to June 2022. Using an appropriate non-probability sampling technique, this cross-sectional study was held at the surgical unit-1 of Khairpur Medical College and civil Hospital Khairpur Mirs. A total of 90 patients, 80 men and 10 women, were selected for the study. Inclusion criteria were defined as patients over 35 years of age with clinical signs such as reducible swelling in the groin area and clinical signs such as overweight and weight lifting. Results: A total of 90 individuals were identified as having an inguinal hernia; their mean age was 26.18± 18.20 years old, and they have 62.78 ± 4.75 inches height. 65.85 ± 5.19 was the patients mean weight and 22.35 ± 3.26 kg/m2 was the mean BMI. BMI was low in 18 (20%) cases and normal in 72 (80%). Conclusion: According to our analysis, a significant number of inguinal hernias on either the right or left side had normal BMIs.